PENGARUH KEGIATAN PAINTING DAN KETERAMPILAN MOTORIK HALUS TERHADAP KREATIVITAS DALAM SENI LUKIS - Selia Dwi Kurnia (FKIP Universitas sriwijaya, 2017)
The purpose of this research were to know the effect of painting activity and fine motor skill toward the creativity of early childhood in painting art of group B of kindergarten. Method in this research used experimental research with treatment design by level 2x2. Sample of this research were 66 students. The prosedure of collecting data used multistage samplingtechnique. Analysis data in this research used two away ANAVA. The result of this research were; 1) the creativity of early childhood in painting are toward thr children who got finger painting was higher than the children who got brush painting, 2) there were interaction beetwen painting activity fine motor skill toward the creativity of early childhood in painting art, 3) the result of children creativity in painting art toward children who had high fine motor skill by giving finger painting activity were higher then children who got brush painting activity, 4) the result of the creativity of early childhood in painting art toward group who had low fine motor skill which was given in finger painting activity was lower than group who was given brush painting activity.